201Sf_1061 - N (1 , c2 c3 ct ) = N [N (c1 ) + N (c2 ) + + N...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon
N c 1 , ¯ c 2 ¯ c 3 ··· ¯ c t ) = N - [ N ( c 1 ) + N ( c 2 ) + ··· + N ( c t )] +[ N ( c 1 c 2 ) + N ( c 1 c 3 ) + ··· + N ( c 1 c t ) + ··· + N ( c 2 c 3 ) + ··· + N ( c t - 1 c t )] - [ N ( c 1 c 2 c 3 ) + N ( c 1 c 2 c 4 ) + ··· + N ( c 1 c 2 c t ) + N ( c 1 c 3 c 4 ) + ··· + N ( c 1 c 3 c t ) + ··· + N ( c t - 2 c t - 1 c t )] + ··· + ( - 1) t N ( c 1 c 2 c 3 ··· c t ) = S 0 - S 1 + S 2 - S 3 + ··· + ( - 1) t S t E m = S m - ± m + 1 1 ! S m +1 + ± m + 2 2 ! S m +2 - ··· + ( - 1) t - m ± t t - m ! S t L m = S m - ± m m - 1 ! S m +1 + ± m + 1 m - 1 ! S m +2 - ··· + ( - 1) t - m ± t - 1 m - 1 ! S t If n Z + , ± - n r ! = ± n + r - 1 r ! For all m, n Z + , a R , (1 + x ) n = ± n 0 ! + ± n 1 ! x + ± n 2 ! x 2 + ··· + ± n n ! x n (1 - x n +1 ) (1 - x ) = 1 + x + x 2 + x 3 + ··· + x n 1 (1 - x ) = 1 + x + x 2 + x 3 ··· = X i =0 x i 1 (1 + x ) n = ± - n 0 ! + ± - n 1 ! x + ± - n 2 ! x 2 + ··· = X i =0 ± - n i ! x i = 1 + ( - 1) ± n + 1 - 1 i ! x + ( - 1) 2 ± n + 2 - 1 2 ! x
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Image of page 2
This is the end of the preview. Sign up to access the rest of the document.

Page1 / 5

201Sf_1061 - N (1 , c2 c3 ct ) = N [N (c1 ) + N (c2 ) + + N...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online